Biomass, carbon and nutrient storage for dominant grasses of cold temperate steppe grasslands in southern Patagonia, Argentina - Peri, Pablo Luis; Lasagno, Romina Gisele (Elsevier, 2022)
We hypothesized that different dominant grasses species display contrasting nutrient accumulation, allocation and conservation strategies. Also, we expect a distinctive pattern of carbon and biomass partitioning according to plant sizes. The aim was to quantify the amount of biomass, carbon and nutrients in both above- and belowground components for four dominant grasses in grasslands steppe. We analyzed biomass, carbon and nutrients (N, P, K, Ca, Mg and S) of each dominant grass species corresponding to different sizes and separated in components (green and senesced leaves, pseudostem, and fine and coarse roots). Total biomass accumulation for individual grass plants was affected by plant size and species and ranged from 15.4 to 684 g dry matter plant1. The biomass root/shoot ratio ranged from 0.28 to 3.40. Total nutrient concentration generally graded in all species the following order: green leaves > fine roots > pseudostem > coarse roots > senesced leaves. Storage of any particular nutrient varied depending mainly on species. Mean nutrient resorption efficiency varied according to the growing season and specie being maximum for K and minimum for Mg. The equations developed for individual grass plants could be used to assist quantitative predictions of biomass, carbon and nutrient accumulation per hectare.